The oxidized low-density lipoprotein/β2-glycoprotein I complex is associated with abdominal obesity in healthy middle-aged men - Kraml, Pavel J; Syrovátka, Petr; Potočková, Jana; Anděl, Michal (Annals of nutrition & metabolism, 2013)
BACKGROUND/AIMS: Oxidized low-density lipoprotein (oxLDL) in complex with β2-glycoprotein I (β2GPI) has been associated with autoimmune diseases, diabetes mellitus, chronic renal disease and coronary atherosclerosis. The aim of our study was to determine whether plasma levels of oxLDL/β2GPI complexes are associated with insulin resistance, inflammation and markers of endothelial damage in obese middle-aged men and, if so, whether oxLDL/β2GPI correlates better with insulin resistance parameters than oxLDL, advanced oxidation protein products (AOPP) or thioredoxin. METHODS: A total of 72 healthy men were recruited (41 obese and 31 nonobese individuals). Waist circumference >94 cm was used as the criterion for abdominal obesity. RESULTS: The obese men demonstrated higher oxLDL/β2GPI levels (p < 0.001), homeostasis model assessment of insulin resistance (p < 0.01) and intima-media thickness of the common carotid artery (p < 0.01). oxLDL/β2GPI correlated with more insulin resistance parameters compared to AOPP, thioredoxin or oxLDL. Furthermore, oxLDL/β2GPI was associated with plasminogen activator inhibitor-I (PAI-I; r = 0.365, p < 0.001) and negatively with interleukin-8 (r = -0.297, p < 0.05). CONCLUSIONS: In summary, oxLDL/β2GPI reflects the criterion for abdominal obesity and markers of insulin resistance in our study. The independent positive correlation with PAI-I indicates that oxLDL/β2GPI may serve as an early marker of low-grade inflammation and atherosclerosis initiation.
Keywords: Oxidative Stress; oxidační stres; Humans; Case-Control Studies; lidé středního věku; Insulin Resistance; studie případů a kontrol; Multivariate Analysis; Thioredoxins; beta-2-glykoprotein I; Waist Circumference; dospělí; Interleukin-8; ateroskleróza; interleukin-8; produkty pokročilé oxidace proteinů; lidé; Biomarkers; abdominální obezita; thioredoxiny; Regression Analysis; Advanced Oxidation Protein Products; Adult; Carotid Intima-Media Thickness; Obesity, Abdominal; lipoproteiny LDL; biologické markery; multivariační analýza; Male; Atherosclerosis; inzulinová rezistence; Middle Aged; beta 2-Glycoprotein I; obvod pasu; inhibitor aktivátoru plazminogenu 1; Lipoproteins, LDL; mužské pohlaví; Plasminogen Activator Inhibitor 1; intimomediální šíře tepenné stěny; regresní analýza